R&D expenditures and the role of government around the world - Bebczuk, Ricardo (Estudios de Economía, 2016)
The goal of this paper is to conduct an empirical investigation on the macroeconomic determinants of research and development (R&D) expenditures and to assess the role of government in the light of recent developments brought about by the endogenous growth theory. The sample comprises 88 countries over the 1980s and 1990s. Our results are broadly consistent with the theoretical predictions, although some striking results are uncovered, namely: (i) trade openness has a negative effect on R&D, but this effect is mitigated as per capita GDP and the trade with OECD countries increase; (ii) investment in R&D is negatively associated to investment in physical capital; (iii) governments fund a higher share of R&D in countries suffering more severe market failures, but they do not compensate for variations in private R&D.